Association of maternal dietary cholesterol intake during the second and third trimesters of pregnancy and blood glucose and pregnancy outcome in women with gestational diabetes mellitus: a prospective cohort study - Xie, Cuiling; Zheng, QingXiang; Jiang, Xiumin; Liao, Yanping; Gao, Xiaoxia; Zhu, Yu; Li, Jianing; Liu, Rulin (Frontiers in Nutrition, 2024)
Background: Cholesterol is very important for pregnant women to maintain maternal health and fetal development. This study aimed to investigate the cholesterol intake of women with gestational diabetes mellitus (GDM) during the second and third trimesters pregnancy, and to explore its effects on blood glucose and pregnancy outcome. Methods: This study was designed as a prospective cohort study. A food frequency questionnaire (FFQ) was used to collected dietary data during the 24-30 gestational weeks as the first survey and the 34-42 gestational weeks as the second survey. Blood glucose indicators and pregnancy outcomes were obtained by querying electronic medical records. Participants were divided into two groups according to the median cholesterol intake including low and high cholesterol intake group. Results: GDM women generally had high cholesterol intake during pregnancy, and cholesterol intake in the third trimester pregnancy was higher than that in the second trimester pregnancy. Compared with women with high cholesterol intake, GDM women with low cholesterol intake had higher risk of abnormal Hemoglobin A1C (HbA1C) during the second [OR 26.014 (95% CI 2.616-258.727)] and third trimesters pregnancy [OR 2.773 (95% CI 1.028-7.482)] and abnormal fasting blood glucose in the third trimester pregnancy [OR 2.907 (95% CI 1.011-8.360)]. Besides, in the second trimester pregnancy, GDM women with high cholesterol intake had higher risks of macrosomia [OR 23.195 (95% CI 2.650-203.024)] and large for gestational age (LGA) [OR 3.253 (95% CI 1.062-9.965)], and lower risks of small for gestational age (SGA) [OR 0.271 (95% CI 0.074-0.986)] than those with low cholesterol intake. However, in the third trimester pregnancy, GDM women with high cholesterol intake had lower risks of macrosomia [OR 0.023 (95% CI 0.001-0.436)] and LGA [OR 0.199 (95% CI 0.042-0.949)]. Conclusion: The cholesterol intake of GDM women during pregnancy was associated with maternal blood glucose, and also significant related with the risks of macrosomia, LGA and SGA. However, cholesterol intake was only one of the factors that affect LGA and SGA, and they were also affected by pre-pregnancy BMI. Cholesterol intake should be limited to help GDM women better control blood glucose and avoid adverse pregnancy outcomes.